Aid, debt burden and government fiscal behaviour in Côte d'Ivoire - Mark McGillivray; Bazoumana Ouattara (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2003)
This paper examines the impact of foreign aid on public sector fiscal behaviour in Côte d'Ivoire. A special interest is the relationship between aid, debt servicing and debt, given that Côte d'Ivoire is a highly indebted country. The theoretical model employed differs from those of previous studies by highlighting the interaction between debt servicing and the other fiscal variables. This model is estimated using 1975-99 time series data. Key findings are that the bulk of aid is allocated to debt servicing and that aid is associated with increases in the level of public debt.
Keywords: 330